2023
DOI: 10.3389/fpls.2023.1196319
|View full text |Cite
|
Sign up to set email alerts
|

Moderate nitrogen application improved salt tolerance by enhancing photosynthesis, antioxidants, and osmotic adjustment in rapeseed (Brassica napus L.)

Long Wang,
Jingdong Zheng,
Guisheng Zhou
et al.

Abstract: Salt stress is a major adverse environmental factor limiting plant growth. Nitrogen (N) application is an effective strategy to alleviate the negative effects of salt stress on plants. To improve the knowledge of the mechanism of N application on alleviating salt stress on rapeseed seedlings, a pot experiment was conducted with four N application treatments (0, 0.1, 0.2, and 0.3 g N kg−1 soil, referred to as N0, N1, N2, and N3, respectively) and exposed to non-salt stress (0 g NaCl kg−1 soil, referred to as S0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In addition to osmotic pressure and ionic stress, salinity induces reactive oxygen species (ROS) overproduction, leading to membrane lipid peroxidation and membrane damage [29]. In contrast, the antioxidant enzyme system, comprising SOD, CAT, and POD, plays an important role in maintaining cellular expansion pressure and scavenging ROS, thus maintaining metabolic homeostasis in plants [30,31]. The results of this study demonstrated an increasing trend of SOD, POD, and CAT contents in celery leaves compared with the pre-treatment values, which is consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to osmotic pressure and ionic stress, salinity induces reactive oxygen species (ROS) overproduction, leading to membrane lipid peroxidation and membrane damage [29]. In contrast, the antioxidant enzyme system, comprising SOD, CAT, and POD, plays an important role in maintaining cellular expansion pressure and scavenging ROS, thus maintaining metabolic homeostasis in plants [30,31]. The results of this study demonstrated an increasing trend of SOD, POD, and CAT contents in celery leaves compared with the pre-treatment values, which is consistent with the previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study observed a decrease in the biomass of different organs at the seedling, flowering, and maturity stages when soil salinity increased. Our previous studies demonstrated that leaf photosynthesis at the seedling and flowering stage was inhibited under salt stress [ 29 , 30 ], leading to a reduction in biomass accumulation. Our findings differed from those of Bakirv et al, who reported that, compared to the non-NaCl condition, the treatment of 100 mM NaCl L −1 showed positive effects on the fresh weight and biomass production in some salt-tolerant varieties [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-enzymatic antioxidant defense mechanisms involve different osmotic substances (amino acids, sugars, etc.) [45]. AsA and GsH, as important non-enzymatic antioxidants, participate in many different metabolic processes of plants and directly affect plant growth [46,47].…”
Section: Exogenous S-aba's Effects On Photosynthetic Efficiency In Ri...mentioning
confidence: 99%